Spiritualitas Ekologi Melalui Musik: Suatu Kajian Terhadap Peran Himne STT GKE Bagi Peningkatan Spiritualitas - Ripaldi; Lantigimo, Enta Malasinta; Josephine Indah Sari (Jurnal Teologi Pambelum, 2025)
Hymns are an essential part of STT GKE’s vision and mission. One aspect of this is the emphasis on the universe as fellow beings, not just humans. Based on this foundation, a study on ecological spirituality through music was conducted, focusing on the role of STT GKE Hymns in enhancing spirituality. The research was carried out from October to November 2024 using qualitative research methods. The study found that, first, hymns serve as a representation of ecological spirituality. Second, hymns reflect the institution’s vision and mission. Third, hymns embody an attitude of service to nature. Fourth, hymns serve as an expression of hope, prayer, and gratitude.